A new eutriconodont mammal from the early Cretaceous Jehol Biota of Liaoning, China - Hou, Shilin; Meng, Jin (Chinese science bulletin, 2014)
A new genus and species of eutriconodont mammal, Chaoyangodens lii gen. et sp. nov., from the Dawangzhangzi bed of Yixian Formation, Lingyuan, Lia- oning, is reported. The new species has a tooth formula I5- C1-P1-M3/i4-cl-pl-m4, unique among eutriconodonts in having only one premolar in lower and upper jaws, respectively, and a distinctive diastema between the canine and the premolar. Its simple incisors and reduced premolars show a mosaic combination of primitive and derived fea- tures. This new taxon adds to the diverse group of Jehol eutriconodonts. Among the known species from at least three horizons, there seems no evolutionary trend in mor- phology that is recognizable, except for that larger species are all from the Lujiatun bed of the Yixian Fro. A thorough and systematic analysis involving all the Jehol eu- triconodonts is needed to understand their phylogenetic relationships.